(untitled) (Fiep Bulletin - online, 2015)
The present study described and analyzed the talent detection process instituted in the Serra Futebol Clube, relating it to the identifying characteristics of the Brazilian soccer, making a parallel between empiricism and scientificity. To do so, we interviewed three professionals who directly work with the detection of talent in the team. The descriptive research based on the direct observation of the activities showed that the applied system does not use the art-soccer as a parameter to select athletes.